1995
DOI: 10.1007/bf02228321
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles emitted by different cotton varieties damaged by feeding beet armyworm larvae

Abstract: Volatile compounds elicited by insect herbivore feeding damage in five cotton cultivars and one naturalized cotton variety were examined by allowing beet armyworm larvae to feed overnight on leaves and collecting volatiles from the plants in situ. Of 23 compounds identified from larval damaged leaves, terpenes and lipoxygenase-hydroperoxide lyase-derived volatiles predominated. No pronounced differences in the levels of volatile emission were noted from leaves of undamaged plants of the different varieties. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(167 citation statements)
references
References 19 publications
5
156
0
6
Order By: Relevance
“…However, genotype specific differences in volatile emissions from undamaged plants have been found in potato (Wang and Kays 2002), rice (Rapusas et al 1996), cotton (Elzen et al 1986) and pear (Scutareanu et al 2003). A high genetic variability in volatile emissions from herbivore-damaged plants has also been shown in cotton (Loughrin et al 1995) and maize (Degen et al 2004;Gouinguené et al 2001). In other plant-herbivore systems, various organic compounds produced in response to plant damage have been shown to affect plant defence and plant gene expression in neighbouring plants, deterring herbivores and attracting their natural enemies (Dicke et al 2003;Baldwin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, genotype specific differences in volatile emissions from undamaged plants have been found in potato (Wang and Kays 2002), rice (Rapusas et al 1996), cotton (Elzen et al 1986) and pear (Scutareanu et al 2003). A high genetic variability in volatile emissions from herbivore-damaged plants has also been shown in cotton (Loughrin et al 1995) and maize (Degen et al 2004;Gouinguené et al 2001). In other plant-herbivore systems, various organic compounds produced in response to plant damage have been shown to affect plant defence and plant gene expression in neighbouring plants, deterring herbivores and attracting their natural enemies (Dicke et al 2003;Baldwin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study also indicated that a single, relatively ubiquitous HIPV can be attractive to A. iole and can lead to increased parasitism. The green-leaf volatile, (Z)-3-hexenyl acetate; the sesquiterpene, α-farnesene; and the carboxylate ester, methyl salicylate, are all produced and released by plants in response to injury by Lygus species (Rodriguez-Saona et al 2002;Blackmer et al 2004;Williams et al 2005) and by other herbivores (Turlings et al 1991;Loughrin et al 1995;Röse et al 1996;Paré and Tumlinson 1998). Thus, it appears that A. iole can use either host-specific or general volatile cues in the process of host habitat location.…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecific variation of herbivore-induced volatile emissions has been reported primarily from varieties of cultivated plants (Loughrin et al, 1995;Geervliet et al, 1997;Gouinguene et al, 2001;Degen et al, 2004;Lou et al, 2006) but has been the subject of only a few investigations of wild species such as solanaceous plants (Halitschke et al, 2000;Glawe et al, 2003;Hare, 2007;Delphia et al, 2009) and teosinte (Gouinguene et al, 2001). In this study, we conducted a survey of 27 Arabidopsis accessions for volatiles released upon treatment with coronalon, a synthetic mimic of octadecanoid plant hormones that induces volatile blends similar to those emitted upon insect feeding (Schuler et al, 2001;Herde et al, 2008).…”
Section: Elicitor-and Insect-induced Volatile Emissions Vary Among Armentioning
confidence: 99%